Dictators' endgames - Croissant, Aurel; Eschenauer-Engler, Tanja; Kühn, David (Oxford University Press, 2024)
Dictators' Endgames examines the political role of the military in "dictators' endgames": large-scale nonviolent mass protests in autocracies that demand the regime leader's removal from office. It addresses the question why some militaries defend an embattled autocrat by violently cracking down on the protestors, whereas others side with the opposition or decide to stage a coup d'état. The book introduces a systematic definition and operationalization of the "dictator's endgame" as a situation of non-violent mass mobilization, in which the dictator's political survival depends on the loyalty of the military leaders. The theoretical argument proposed in this book focuses on the strategic calculations of military leaders and offers a systematic explanation why the armed forces opt for repression of the demonstrators, shift their loyalty from the dictator to the opposition, or remove the autocrat in a coup during the mass protests. The theory's predictions are empirically tested in a multi-method research design that combines statistical analyses and case studies, drawing on the original Dictator's Endgame Dataset of all 40 endgames that took place between 1946 and 2014. The study identifies the conditions and processes through which militaries determine the outcome of dictators' endgames, and thus affect the survival and future political development of authoritarian regimes.
Quellen- und Literaturverzeichnis: Seite 197-228, Register
Keywords: Militär; Protestbewegung; Autoritärer Staat